Pengembangan Bahan Ajar Tematik Terpadu dengan Model Cooperative Script di Kelas IV Sekolah Dasar - Dahliana, Dina; Remuti, Remuti (ZAHRA: Research and Tought Elementary School of Islam Journal, 2021)
Teachers are very instrumental in developing effective teaching materials to encourage the progress of students in learning. Meanwhile, the existing teaching materials still need improvements because there are several errors such as paragraphs in the reading text that are not aligned left-right, errors in capital letters. Therefore, to solve this roblem, it is necessary to find a solution in the form of developing integrated thematic teaching materials based on the cooperative script model for grade IV elementary school students. This study aims to produce valid teaching materials. This type of research is development research using the 4-D model (four D model). This model consists of four stages, namely define, design, develop and disseminate. The results showed that the integrated thematic teaching materials using the cooperative script model developed obtained the validity percentage of teaching materials was 87.5% (material) with a very valid category, 75% (language) with a valid category, and 81.8% (design) with very valid category.